2009
DOI: 10.1002/anie.200805604
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydroboration of 1,1‐Disubstituted Alkenes

Abstract: A breakthrough in the asymmetric hydroboration of notoriously difficult 1,1-disubstituted alkenes using a new family of highly effective hydroboration reagents is described (see scheme). The intermediate boranes can be oxidized to alcohols or used in Suzuki-Miyaura cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 23 publications
1
67
0
2
Order By: Relevance
“…The enantioselective anti-Markovnikov hydroamination of 1,1-disubstituted alkenes represents an attractive route for the synthesis of this type of amine, but a process to effect this transformation remained elusive due to the low reactivity of 1,1-disubstituted alkenes towards many transition metal catalyzed processes, as well as the relatively undifferentiated nature of the enantiotopic faces of these substrates. [32] In 2014, Buchwald reported that the DTBM-SEGPHOS-based CuH catalyst system was able to facilitate this transformation. [33] Excellent levels of enantioselectivity were observed when there was a significant difference in size between the two substituents of the 1,1-disubstituted alkene (25–27, Scheme 12).…”
Section: Copper(i) Hydride-catalyzed Hydroamination – Discovery Smentioning
confidence: 99%
“…The enantioselective anti-Markovnikov hydroamination of 1,1-disubstituted alkenes represents an attractive route for the synthesis of this type of amine, but a process to effect this transformation remained elusive due to the low reactivity of 1,1-disubstituted alkenes towards many transition metal catalyzed processes, as well as the relatively undifferentiated nature of the enantiotopic faces of these substrates. [32] In 2014, Buchwald reported that the DTBM-SEGPHOS-based CuH catalyst system was able to facilitate this transformation. [33] Excellent levels of enantioselectivity were observed when there was a significant difference in size between the two substituents of the 1,1-disubstituted alkene (25–27, Scheme 12).…”
Section: Copper(i) Hydride-catalyzed Hydroamination – Discovery Smentioning
confidence: 99%
“…1 Previously, high selectivity was the sole preserve of macromolecular structures, like enzymes. Although historically significant, and practical at the time, this method has been largely superseded by methods involving asymmetric metal catalysis, principally rhodium- and copper-catalyzed processes.…”
mentioning
confidence: 99%
“…6 The direct access to branched boranes from the hydroboration of terminal olefins is typically accompanied by chain walking 7 that often leads to terminal or benzylic boranes. Advances in reversing the regiochemical outcome of hydroborations are often accomplished through the installation of directing groups, which can override normally expected preferences based on the alkene substitution pattern.…”
mentioning
confidence: 99%